Challenges in the Implementation of Internet of Things (IoT) in Irrigation and Fertilizer Management System in Indonesia - Kushendarsyah Saptaji; Azahri Tumada; Muhamad Lukman Baihaqi Alfakihuddin; Dilla Ayu Wardani; Tiara Kusuma Dewi; Octarina Adiati Junaisih; Muhamad Rausyan Fikri; Muhammad Sobirin Hendrawan Achmad (Jurnal Keteknikan Pertanian, 2025)
Agriculture is critical to many countries' economies, especially related to gross domestic products (GDP) and employment. However, as a result of industrialization, leading to a problem in fulfilling the expanding global food supply demand. The Internet of Things (IoT) can enhance automatic data transfer in agricultural, improve production, increase quality, improve cost-effectiveness, and reduce environmental impact. However, the obstacles related to IoT application in agriculture have received little discussion especially in the development countries such as Indonesia. This research seeks to fill that gap by investigating the specific issues of adopting the Internet of Things (IoT) in the context of an irrigation and fertilizer management system in Indonesia. To fully study this, a stratified multistage random sampling was conducted to acquire significant insights and data. According to the interview results, respondents voiced worries regarding IoT deployment in agriculture, including, costs implementation (CI), their own knowledge (perceived knowledge (PK)), user experiences with the technology (perceived ease of use (PEU)) and intention of use (IU). The study finds weak CI-IU and PK-IU links but a strong PEU-IU correlation, underscoring the multifaceted factors influencing IoT adoption in agriculture. It is found that the easiness of the use of IoT is the main factors that influence Indonesian farmers to implement the IoT in their farmers. Although the cost of the implementation is an essential factor, easiness to use IoT is the most significant factor. Lastly, researchers, policymakers, and agricultural stakeholders can leverage these insights to advance IoT integration and sustainability in farming practices.